Pathways to understanding the genomic aetiology of osteoarthritis - Cibrián Uhalte, Elena (Hum Mol Genet, 2017)
Osteoarthritis is a common, complex disease with no curative therapy. In this review, we summarize current knowledge on disease aetiopathogenesis and outline genetics and genomics approaches that are helping catalyse a much-needed improved understanding of the biological underpinning of disease development and progression.